2012
DOI: 10.1016/s2255-4971(15)30112-9
|View full text |Cite
|
Sign up to set email alerts
|

Navigated Versus Mechanical Knee Replacement: Comparison Between Initial Navigated and Conventional Cases Performed by the Same Surgeon

Abstract: Objective: The postoperative mechanical axis in 36 cases of total knee arthroplasty using navigated and mechanical alignment systems was evaluated and compared. All the operations were performed over the same period by the same surgeon and team, who were beginners in the navigated technique and experienced in the mechanical technique. Methods: Between 2008 and 2010, 36 total knee prostheses were performed and compared: 25 navigated and 11 mechanical procedures. Any deviation from the axis measured on the panor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
(39 reference statements)
1
3
0
Order By: Relevance
“…Similar finding with our study was also observed in study by Pacheco et al 16 In their study, the surgeon was already expert in conventional TKA, but had just been trained in computerassisted navigation TKA. This situation is also reflected in our study.…”
Section: Discussionsupporting
confidence: 93%
“…Similar finding with our study was also observed in study by Pacheco et al 16 In their study, the surgeon was already expert in conventional TKA, but had just been trained in computerassisted navigation TKA. This situation is also reflected in our study.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, disabling these nerve fibers by electrocautery could, in theory, achieve a satisfactory level of denervation and, consequently, reduce local pain. 1,6 Studies have shown a positive effect of patellar denervation in reducing the incidence of AKP. 7,8 A recent meta-analysis demonstrated that patellar denervation…”
Section: 3mentioning
confidence: 99%
“…1 This procedure has become quite common, especially in the last two decades due to the aging of population and to the growing number of obese people. undergoing surgery will show these symptoms.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation